Comparison and other “Modes of Order” in the plays of Bernard Shaw - Rodríguez Martín, Gustavo A. (International Journal of English Studies, 2012)
Bernard Shaw is widely regarded as one of the most important playwrights in the English language, ranking often second only to Shakespeare. This literary prominence, however, is not matched by a significant number of stylistic analyses, much more so in the case of linguistically-oriented ones. One of the few studies in Shaviana with a clear stylistic approach is Ohmann’s (1962) monograph. However, it focuses on Shaw’s non-dramatic writings and, due to its publication date, it does not utilize software tools for corpus stylistics. The purpose of this paper is to analyze Bernard Shaw’s use of certain comparative structures in his dramatic writings (what Ohmann calls ‘Modes of Order’ in his book) with the aid of the technical and methodological advances of computer-based stylistics, thus utilizing an innovative outlook because of the combination of stylistics and corpora research.